Evaluation of Double Loop IC Module for Inductive Coupled Fed RFID Tag Wire Embedded Antenna - N. A. Murad; M. H. M. Salleh; N. Q. Azmi; A. R. Tanvir; A. A. Z. A Nizam (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
This paper presents an evaluation on double loop integrated circuit module for inductive couple fed RFID Tag. The inductive couple feed gives advantage especially for flexible wire embedded antenna in controlling the manufacturing varians as the chip is not directly connected to the antenna. Thus electrostatic discharged effect and manufacturing errors can be minimized. An inductor loop is directly connected to the RFID chip before it is placed to indirectly coupled the energy from a meandered dipole antenna. The coupled energy should be enough to turn on the chip to communicate with the reader. The inductive coupled energy is achieved by manipulating the near field magnetic field between the antenna body and the inductor loop. To evaluate the performance, the antenna and the inductive feeding loop is designed to operate at RFID UHF band (860 MHz – 960 MHz) and simulated using CST software. The antenna body impedance is evaluated to match the impedance of the chip and the loop. It is confirmed that the double loop inductor has higher inductance values and thus should be counted in conjugate impedance between the antenna body and the chip module. The tag with overall dimension of 60 mm x 16 mm can be read at distance at least 9 meters through out the band.